THE COHERENCE AND UNITY IN STUDENTS’ WRITING DESCRIPTIVE TEXT (Descriptive Study at Private Junior High School in East Jakarta) - Putri Dwijayanti; Syahfitri Purnama (Universitas Indraprasta PGRI, 2020)
Abstract: This study was conducted to analyze the coherence and unity of the paragraphs written by students in their descriptive text. The method of the study was descriptive analysis by using content analysis. The result of the research stated that: (1) the students’ writings are coherent. It could be seen in pronoun, anaphora, cataphora, repetition key noun, transition signal, and logical order are well organized. (2) the texts are not unified. They were able to state a clear topic discussion in the first sentence but couldn’t maintain the topic in all of the supporting sentences. They were lack of related supporting details in discussing the topic of the paragraph. The common errors made by the students are from the inconsistent topic, not logical order sentences, redundant sentences, and unrelated sentences. It can be concluded that the students were success to make coherent paragraphs, but they were failed to make unified paragraphs.Keywords: coherence; unity; students’ writing Descriptive text.